EFEKTIVITAS PELAKSANAAN KEBIJAKAN PENGURANGAN PENGGUNAAN KANTONG PLASTIK DI KOTA SUKABUMI - Ghifary Prinardi; Dian Purwanti; Yana Fajar FY Basori (Kebijakan : Jurnal Ilmu Administrasi, 2023)
Waste is a major pollution problem both globally and nationwide. One type of waste that is inherently persistent and harmful to human health is plastic waste. Plastic is one of the materials found in almost every item. The Government of Sukabumi city has stipulated the Mayor's Regulation No. 19 of 2019 about reducing the use of plastic bags in order to minimize the generated plastic waste, prevent environmental pollution caused by plastic waste and maintain environmental sustainability. The research used one variable, namely effectiveness, and applied the policy effectiveness theory proposed by Nugroho (51-54:2021) consisting of right policy indicators, right implementation, right target, right environment, and right process). The research employs one variable (1), the effectiveness variable.This research uses a Mixed Methods approach with a Conccurent Triangulation model. The research also deployed the z-test analysis technique. The result of the research on the level of policy effectiveness shows that the use of plastic bags reduction policy in Sukabumi City is considered to be very effective, gaining a percentage of 87.53%. Moreover, the result of the z-test acquires a calculated z value of 0.151, meaning that in the research, the result of the z-test is greater than the z-table namely amounted to 0.05; therefore, H1 is accepted, indicating that the effectiveness of the use of plastic bags reduction policy in Sukabumi City is effective